The effect of central and local governmental policies on the lives of the aged and infirm in Mangaung, Bloemfontein, 1940-1986 - Le Roux, Charl (Faculty of Humanities, University of the Free State, 2009)
Abstract not available
Keywords: Govermental policies; Local government; Social security; South African government; Socio-economic conditions